EFFECT OF POTASSIUM SOURCES ON SOME POTATO CULTIVARS GROWN IN SANDY SOIL BY USING PIVOT IRRIGATION SYSTEM - Mousa, T. A.E,; Samar, A. Bardisi,; H. E. M. Esmail,; G. A. Zaed, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Study  was carried out during two successive summer seasons of 2021 and 2022 at private  filed  in El-Salhyia El-Gadida District, Sharkia Governorate, to study response of some potato cultivars to potassium sources as foliar application  under sandy soil conditions using pivot  irrigation system. This experiment included 25 treatments, which were the combinations between five potato cultivars (Spunta , Santana , Cara , Lady  Rosetta  and Hermes) and  four  potassium  sources treatments , i.e. spraying with potassium silicate (KSil , (potassium citrate (KCit), potassium folvate (KF) and potassium thiosulpahte (KTS) as well as control (without spraying). These treatments were arranged in a split plot design with three replicates. Potato cultivars were randomly arranged in the main plots and  potassium sources  were randomly distributed in the sub plots. Spraying Cara cultivar with KCit increased number of tubers/ plant and total  yield /hectare, whereas  spraying  Spunta  cultivar with KCit increased average tuber weight in both seasons. While, spraying Hermes cultivar with   KSil as foliar spray increased DM, starch and total carbohydrates in tubers. Spunta cultivar with water only increased total sugars in tubers.  In addition, the fertilization of Cara cultivar   with  KCit as a foliar application recorded a relative increase in the total yield of tubers amounting to about 72.50% as an average of the two seasons compared to the same cultivar  without.